Concept of effective Control among the Means of Restoring National Security of Ukraine - O. V. Cherviakova; R. V. Sytnyk; M. M. Honcharenko (Law and Safety, 2021)
The sovereignty and territorial integrity of Ukraine have been violated for more than seven years, part of the territories of Donetsk and Luhansk regions, the Autonomous Republic of Crimea are temporarily not under the control of the sovereign. Researchers and reintegration experts pay attention to the categories of effective and general control in these circumstances. Both concepts from the point of view of historical and law-making importance have significantly influenced the development of international public law and the state responsibility institution involved in armed conflicts, but accomplish this not directly, but through third parties of the conflict: a state controls the behavior of individuals or groups of individuals on the territory of another state. It is possible to appropriate the actions of individuals to the state through the concepts of state and effective control at the international level, although such evidence is extremely difficult in some cases, since the relationship is carefully concealed and the state denies its involvement in international armed conflict. The establishment and recognition of such a relationship between a state and a person or a group of persons, as well as the disclosure of the causal link between governmental actions and the conduct of individuals becomes the subject matter of proving at the international level in case of applying the concepts of effective and general control. In particular, the United Nations International Court of Justice and the European Court of Human Rights are actively working with the concepts of effective and general control to deal with cases of violating human rights, international humanitarian law on the territories of armed conflict.